Asian yearbook of international law. - Chimni, B. S., 1952-; Miyoshi, Masahiro; Thio, Li-ann (Routledge, 2010)
Launched in 1991, the Asian Yearbook of International Law is a major refereed publication dedicated to international law issues as seen primarily from an Asian perspective, under the auspices of the Foundation for the Development of International Law in Asia (DILA) It is the first publication of its kind edited by a team of leading international law scholars from across Asia. The Yearbook provides a forum for the publication of articles in the field of international law, and other Asian international law topics, written by experts from the region and elsewhere.